Application of phase change materials in solar water heating systems for thermal energy storage - Nagilla, Dheeraj Kumar; V. V., Tyagi; Kumaran, Kadirgama; K., Chopra; A. K., Pandey; Kothari, Richa (IOP Publishing, 2021)
One of the major drawbacks of solar water heating systems is unable to supply hot water during night time or off sunshine hours. The integration of phase change material with solar water heating systems is cost effective and efficient solution to overcome this major problem associated with solar water heating systems. The phase change material integrated with solar water heating system stores thermal energy during sun shine hours and this stored energy can be recovered during off shine hours or night time to produce hot water. The phase change material can be integrated with water tank of collector, evacuated tubes, external water tank for solar collector and flat plate collector by adding layers at the bottom of absorber plate. The integration of phase change material with SWH system not only overcome the drawbacks of SWH system but also enhance the efficiency of conventional SWH system. Many investigations for the application of TES materials integrated SWH system have been carried out and found a significant enhancement in the performance. This paper presents a comprehensive review of recent advances in the applications of PCM with SWH system for TES